Taking sides clashing views on moral issues - Satris, Stephen (McGraw-Hill contemporary learning series, 2012)
Presents the various controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. This title frames each issue with an issue summary, an issue introduction, and a postscript. It features an annotated listing of selected World Wide Web sites